2020
DOI: 10.32479/ijeep.9003
|View full text |Cite
|
Sign up to set email alerts
|

Energy Industry Performance in Saudi Arabia: Empirical Evidence

Abstract: This study aims at investigating the associations of board of directors' size, board of directors' meetings, firm size and firm leverage with firm performance among energy industry in Saudi Arabia for periods ranging from 2005 to 2018. The final sample in this study consists of 56 observations. The ordinary-least square regression shows that board size is associated positively with firm performance. Further, the results of this study repot that board meetings, firm size and firm leverage are associated negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…4. Board members are significant stakeholder of the company (Aljaaidi and Hassan, 2020). The hypothesis of this research can be written below as.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…4. Board members are significant stakeholder of the company (Aljaaidi and Hassan, 2020). The hypothesis of this research can be written below as.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Likewise, Tanveer et al (2016) showed that liquidity significantly affects company's economical health that is listed on the Karachi Stock Exchange. Aljaaidi and Hassan (2020) uncovered a beneficial connection amongst board sizes and business outcome in Saudi Arabia. Additionally, Shaik (2021) observed that larger companies tend to be more profitable.…”
Section: Literature Regarding Determinants On Company Performancementioning
confidence: 99%
“…Finally, they found that financial performance is governed by the working capital. Aljaaidi and Hassan (2020) studied and found that the size of the board is positively associated with firm performance. Further, they demonstrated that, in the context of Saudi Arabia, board meetings, firm size, and firm leverage are inversely correlated with firm performance.…”
Section: Literature Reviewmentioning
confidence: 99%